CORE SKILLS IN SOCCER: A STUDY OF BASIC DRIBBLING, PASSING, AND SHOOTING TECHNIQUES IN YOUTH PLAYERS - Toktong Parulian; Roiyatul Ruqayah; Oki Candra (YLPK Mahardhika, 2026)
This study aimed to analyze the core soccer skills consisting of dribbling, passing, and shooting among youth players. The study employed a quantitative approach with a descriptive research design. The research subjects consisted of 30 youth soccer players aged 10–12 years who participated in a soccer development program. Data collection was conducted using basic soccer skill tests, including dribbling, passing, and shooting assessments. The data were analyzed using descriptive statistics in the form of mean, standard deviation, minimum and maximum values, frequencies, and percentages. The results showed that the players’ dribbling ability was categorized as good, with an average score of 15.43 seconds. Passing ability obtained an average score of 12.37 and was also classified as good. Meanwhile, shooting ability achieved an average score of 8.33 and was categorized as good to moderate. Players aged 12 years demonstrated better technical performance than players aged 10 years, particularly in dribbling speed, passing accuracy, and shooting effectiveness. The findings indicated that the development of basic soccer technical skills was influenced by age, training experience, motor coordination, and the quality of training programs. This study emphasizes the importance of systematic, repetitive, and age-appropriate basic technical training to improve the performance of youth soccer players. The findings may serve as a reference for coaches in designing more effective and structured soccer technical training programs.